Testosterone role during seasons changes in the dogs testes: Najlaa Sami Ibrahim and Nazih Wayes Zaid - Zaid, Nazih Wayes (The Iraqi Journal of Veterinary Medicine, 2017)
This study was conducted to evaluate the effect of seasons on serum testosterone level, testis histology examination and testosterone receptors by using cytoimmunochemistry techniques. Samples of blood and both testes were collected from 24 local dogs aged between 2-3 years and weighted 18-22 kg. This study carried out at 2015, divided into four seasons. No differences in testosterone level were observed between seasons. However, histological examinations were characterized by significant (P<0.01) changes during seasons in tubular diameters, germinal thickness and tubular area. Cytoimmunochemistry investigation showed differences between seasons also, there was a distributions of testosterone hormone receptors in the Leydig cells, Sertoli cells and in germinal epithelium during spring and autumn, at the same time the winter season showed distribution of testosterone hormone receptors in Leydig and Sertoli cells only. The summer season characterize by diffuse of receptors in Leydig cells only. In conclusion there was a significant effect of season on testis of dog in Iraq, the summer season was the lowest in reproductive activity while the spring and autumn season was the highest of reproductive activity of dog in Iraq.